Epidermal Lignin Deposition in Quinoa Cotyledons in Response to UV-B Radiation - Hilal, Mirna Beatriz (2007)
UV-B radiation (280–320 nm) is harmful to living organisms and has detrimental effects on plant growth, development and physiology. In this work we examined some mechanisms involved in plant responses to UV-B radiation. Seedlings of quinoa (Chenopodium quinoa Willd.) were exposed to variable numbers of UV-B radiation doses, and the effect on cotyledons was studied. We analyzed (1) cotyledons anatomy and chloroplasts ultrastructure; (2) peroxidase activity involved in the lignification processes; and (3) content of photosynthetic pigments, phenolic compounds and carbohydrates. Exposure to two UV-B doses induced an increase in the wall thickness of epidermal cells, which was associated with lignin deposition and higher activity of the peroxidase. The chloroplast ultrastructure showed an appearance typical of plants under shade conditions, likely in response to reduced light penetration into the mesophyll cells due to the screening effect of epidermal lignin deposition. Exposure to UV-B radiation also led to (1) enhancement in the level of phenolics, which may serve a protective function; (2) strong increase in the fructose content, a fact that might be related to higher requirement of erythrose-4P as a substrate for the synthesis of lignin and phenolics; and (3) reduction in the chlorophyll concentration, evidencing alteration in the photosynthetic system. We propose that the observed lignin deposition in epidermal tissues of quinoa is a resistance mechanism against UV-B radiation, which allows growing of this species in Andean highlands.